The battle for working-class souls in the 19th century. Primary education in the urban sphere of liberal Spain: a case study - Page Campos, Eduard (Historia y Memoria de la Educación, 2024)
The efforts of the nineteenth-century liberal elites to promote childhood education among popular classes had a complex translation into the Spanish social reality. In order to study the initiatives for childhood education and the reality of schools and teachers in nineteenth-century urban Spain, this article undertakes a micro-analysis of a specific working-class urban space, Barceloneta. Precariousness and poor conditions were the dominant characteristics of the municipal schools opened in 1841. In fact, all educational initiatives, including those of a public nature, had as their main purpose the moralisation of a neighbourhood perceived as alien and potentially dangerous by the urban elite. This intensified from the 1870s onwards, when Barcelona’s port district became a key stage in the ideological battle for the control of working-class souls. This battle allowed the multiplication of private schools, which would end up covering most of the pupils, contrary to the Spanish trend. The battle for the spiritual control of the district, at least in the field of formal education, was won by the Catholic Church. As a result of the process, the schooling rate saw a clear improvement at the end of the century. To a lesser extent, literacy rates also improved, although according to the micro-analysis of census data carried out, this progress must be associated with informal or semi-formal education processes rather than with formal instruction.